(untitled) (Research, Society and Development, 2021)
Aim: This study aimed to analyze the prevalence of Sexually Transmitted Infections (STI) in university students of a public institution in Parnaíba. Methods: The research was a descriptive, cross-sectional and inferential study with a quantitative approach carried out from May 2020 to February 2021, using the online tool Google Forms. It had a sample of 286 volunteers aged between 18 and 38 years. For data analysis, descriptive statistics and the Chi-square test were used. Results: The results showed that the prevalence of STIs in the last 12 months was 33.2%, with 3.8% of these occurring during the research period, and only 14.0% sought health care. Only 33.2% reported that they almost always use a condom. About sexual education, 65% mentioned contact with the subject. However, it was not decisive in preventing STIs, which of the mentioned, the most common were candidiasis, syphilis, HPV and gonorrhea. Conclusion: The percentages found in this study show a moderate prevalence of STIs in the young population under study, as well as a protection for those who use condoms during vaginal and oral sex.